Genetic variations and carcinogenicity analysis of E6/E7 oncogenes in HPV31 and HPV35 in Taizhou, China - Hao-Bo Yuan; Jun-Hui Yu; Jun Gan; Yi Qiu; Zi-Yi Yan; Hui-Hui Xu (Virology Journal)
Abstract Background The purpose of this study was to investigate the genetic variations in the E6 and E7 oncogenes of HPV31 and HPV35, and to explore their potential role in cervical cancer risk among women in Taizhou, China. Methods Cervical exfoliated cells were collected for HPV genotyping, and only patients with a single infection of either HPV31 or HPV35 were selected for this study. The ABI 3730xl sequencer was utilized to sequence the E6 and E7 genes, followed by subsequent sequence alignment, analysis of genetic heterogeneity, and construction of maximum likelihood phylogenetic trees for the sequences of HPV31 and HPV35 using BioEdit and MEGA softwares. Results From 2013 to 2023, 148 HPV31 E6/E7 gene sequences and 121 HPV35 E6/E7 gene sequences were successfully obtained. We identified 16 distinct HPV31 E6/E7 variants and 5 distinct HPV35 E6/E7 variants, which have been deposited in GenBank under accession numbers OR540563-OR540578 and OR540579-OR540583, respectively. Phylogenetic analysis revealed that most of the HPV31 variants belonged to sublineage A2 (57.4%), followed by sublineages C2 (26.4%), C3 (14.2%) and B1 (2.0%). The proportion of CIN2 + patients in sublineage A2 was greater than that in other HPV31 sublineages, but the difference was not statistically significant (69.2% vs. 30.8%, P > 0.05). The most common variant in A2 was 31CNTZ07, which has a greater risk of CIN2 + than other A2 variants (OR = 3.5, 95% CI = 1.31 to 9.36; P < 0.05). In addition, all the HPV35 variants belonged to lineage A, of which 99.2% belonged to sublineage A1. 35CNTZ01 and 35CNTZ03 were the two most common HPV35 variants in our population, but no significant difference in their carcinogenic ability was observed (P < 0.05). Conclusion These data provides a deeper insight into the distribution of geographic/ethnical HPV31 and HPV35 variants, which contribute to the development of multivalent HPV vaccines and diagnostic assays that are suitable for Chinese women.